Barriers to reusing and recycling office fit-out: an exploratory analysis of demolition processes and product features (Construction Economics and Building, 2020)
Within the highly waste-generative context of Australia, waste from demolition of office fit-out significantly contributes to unsustainable landfilling. The extant literature is, however, slim on scrutiny of the situation. Therefore, this study aims to uncover office fit-out demolition processes and product features that drive high ratio of landfilling fit-out elements. The research used ten case projects and fourteen interviews to document visible and latent parameters of office fit-out waste. Waste-stream mapping and decision-tree techniques, in conjunction with basic descriptive statistics, were used to model and visualize the extent and drivers of unsustainable fit-out demolition. Further, an exemplar product features analysis was conducted to validate the identified drivers. The findings show that 78% of fit-out waste from the studied cases is landfilled. This high rate is attributed to both latent and visible factors. The main latent factor is high lease price of premium or high-quality offices which favours expeditious demolition with low consideration for reuse and recycling. Key technically visible barriers are volumetric furniture, heterogeneous fit-out assemblies, and insufficient critical mass. To move away from landfilling, production of office fit-out should be transformed for sustainable material adequacy, product re-configurability and de-constructability, and easy handling in the use phase.